2017
DOI: 10.1158/0008-5472.can-16-1373
|View full text |Cite
|
Sign up to set email alerts
|

IL6 Signaling in Peripheral Blood T Cells Predicts Clinical Outcome in Breast Cancer

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine with both pro- and anti-inflammatory properties which acts directly on cancer cells to promote their survival and proliferation. Elevated serum IL-6 levels negatively correlate with survival of cancer patients, which is generally attributed to the direct effects of IL-6 on cancer cells. How IL-6 modulates the host immune response in cancer patients is unclear. Here we show the IL-6 signaling response in peripheral blood T cells is impaired in breast cancer (BC) pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…It is continuously produced and secreted by various types of cells including T cells, endothelial cells, macrophages, and tumor cells themselves . Many clinical studies independently reported a significant correlation between the concentration of IL‐6 and patient prognosis in various cancer types . In concordance with these studies, our study also documented that a high concentration of preoperative serum IL‐6 is associated with negative prognosis among patients with hepatic side T2 GBC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is continuously produced and secreted by various types of cells including T cells, endothelial cells, macrophages, and tumor cells themselves . Many clinical studies independently reported a significant correlation between the concentration of IL‐6 and patient prognosis in various cancer types . In concordance with these studies, our study also documented that a high concentration of preoperative serum IL‐6 is associated with negative prognosis among patients with hepatic side T2 GBC.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that IL‐6‐mediated activation of the JAK‐STAT3 signaling pathway is a principal pathway implicated in tumor formation and metastatic progression . Clinically, the predictive ability of serum IL‐6 was observed in several types of tumors, including breast cancer, lung cancer, renal cell carcinoma, hepatocellular carcinoma, bladder cancer, prostate cancer, and pancreatic cancer . More importantly, some preclinical and translational findings suggested that IL‐6 signaling blockade may have therapeutic indications in some of the cancers mentioned above, including ovarian clear cell adenocarcinoma, progressive metastatic renal cell carcinoma, and metastatic castration‐resistant prostate cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it shows a critical role for IL-6 in promoting TNFR2 expression on T cells, and particularly on Tregs. These findings could provide a mechanistic link between IL-6 and Tregs, where both have been independently associated with disease progression, for example in breast, lung, renal, and colorectal cancer ( 80 83 ). These results also suggest that IL-6 blocking therapy may have additional beneficial therapeutic effects ( 62 ).…”
Section: Discussionmentioning
confidence: 93%
“…Cytokines participate in many physiological processes, mostly in the regulation of immune and inflammatory responses (Ai et al, 2013). Interleukin-6 (IL-6) is a pleiotropic cytokine (inflammatory and anti-inflammatory properties) able to modulate the activity of immune cells (Wang et al, 2017). Tumor necrosis factor-α (TNF-α) is a pro-inflammatory cytokine released from macrophages or activated T cells which plays a crucial role in many immune and inflammatory processes, such as proliferation, apoptosis, and cell survival (Cai et al, 2017).…”
Section: Lps-free Chitosan Nanoparticles Do Not Stimulate Il-6 and Tnmentioning
confidence: 99%